A method for locating abnormal sound in transmission line channels based on time delay estimation and equipment coordinates. Issue 1 (1st December 2022) - Sun, Xiaobin; Cai, Fudong; Yang, Jie; Guo, Guoxin; Liu, Huanyun; Liu, Xiaoqing; Kong, Zhiqiang; Lv, Changfeng
Abstract: To get rid of the current transmission line visual monitoring device which only relies on a single photo-monitoring method, this paper proposes a method based on time-delay estimation and equipment coordinates to locate abnormal sound in the transmission line channel. Firstly, the audio-visual equipment is selected to collect the abnormal sound information of any transmission line as the reference warning record, and the relative time difference between other warning records and the reference warning record is determined. Then, the corresponding audio-visual equipment of the reference alarm record is used as a reference point to set up a Cartesian coordinate system, obtain the GPS information of other audio-visual equipment, unify the GPS information, and get the coordinates of other audio-visual equipment; finally, based on the reference point coordinates, other audio-visual equipment coordinates, and the relative time difference, the transmission channel abnormal sound source coordinates are obtained. Through the experiment of firecracker sound, we can get the firecracker sound within 2km in the open environment, which proves that the location method can effectively enhance the monitoring effect of the transmission channel.